Genetic Progress of Seed Yield and Nitrogen Use Efficiency of Brazilian carioca Common Bean Cultivars Using Bayesian Approaches - Zeffa, Douglas Mariani; Moda-Cirino, Vânia; Medeiros, Isabella Arruda; Freiria, Gustavo Henrique; Neto, José dos Santos; Ivamoto-Suzuki, Suzana Tiemi; Delfini, Jéssica; Scapim, Carlos Alberto; Gonçalves, Leandro Simões Azeredo (Frontiers in Plant Science, 2020)
Common bean is an important crop worldwide, especially for tropical countries that include common beans in their daily diet. The reduction of chemical fertilizers is a global challenge, and the development of cultivars more nitrogen use efficiency (NUsE) is considered one the main strategies to reduce the amount of N fertilizers. In this study our goal was to analyze the genetic progress of seed yield (SY) and NUsE-related traits of 40 carioca common bean cultivars release from 1970 to 2017 in eight environments under low (zero) or high N (40 kg ha–1) in top-dressing. Genetic progress, principal component analysis, correlations among traits and cultivars stability were analyzed using Bayesian approaches. The lowest values of the deviance information criterion (DIC) for the full model tested indicated the presence of the genotype × N × environment interaction for all evaluated traits. Nitrogen utilization efficiency (NUtE) and nitrogen uptake efficiency (NUpE) were the traits that most contributed to discriminate cultivars. The genetic progress of SY under high N (0.53% year–1, 95% HPD = 0.39; 0.65% year–1) was similar to that obtained in low N conditions (0.48% year–1, 95% HPD = 0.31; 0.64% year–1). These results indicate that modern cultivars do not demand more N fertilizers to be more productive. In addition, we observed a high genetic variability for NUsE-related traits, but there was no genetic progress for these variables. SY showed negative correlation with seed protein content (Prot) in both N conditions, and there was no reduction in Prot in modern cultivars. Both modern and old cultivars showed adaptability and stability under contrasting N conditions. Our study contributed to improve our knowledge about the genetic progress of common bean breeding program in Brazil in the last 47 years, and our data will help researchers to face the challenge of increase NUsE and Prot in the next few years.